Heavy resistance training is safe and improves bone, function, and stature in postmenopausal women with low to very low bone mass: novel early findings from the LIFTMOR trial. Issue 12 (December 2015) - Watson, S.; Weeks, B.; Weis, L.; Horan, S.; Beck, B.
Abstract Summary The aim of the LIFTMOR (Lifting Intervention For Training Muscle and Osteoporosis Rehabilitation) trial is to determine the safety and efficacy of brief, bone-targeted, high-intensity progressive resistance training (HiPRT) with impact loading for postmenopausal women with low bone mass. Preliminary findings indicate the LIFTMOR program is safe and effective. Introduction Despite a lack of notable efficacy, exercise guidelines for osteoporosis typically recommend moderate-intensity exercises, owing to a perceived risk of fracture from high-intensity loading. Indeed, safety concerns alone have prevented the well-recognised preferential response of bone tissue to high-intensity loads from being applied to those who stand to benefit the most. To progress from this therapeutic stalemate, a challenge to conventional wisdom was required. Our goal was to examine the safety and efficacy of HiPRT and impact loading for risk factors of osteoporotic fracture in postmenopausal women with low to very low bone mass. Methods Participants have been randomised to either 8 months of twice-weekly 30-min supervised HiPRT and impact loading or a low-intensity home-based exercise program of the same duration and dose. Testing at baseline and follow-up has included anthropometry; bone, muscle, and fat mass; and functional performance. Results Twenty-eight women (66.1 ± 4.8 years, mean lumbar spine T-score −2.15 ± 0.72) have completed the study. HiPRT and impact loading (n = 12) improved height (0.4 ± 0.2 cm vs −0.3 ± 0.1 cm, p = 0.003), femoral neck bone mineral density (0.3 ± 0.5 % vs −2.5 ± 0.8 %, p = 0.016), lumbar spine bone mineral density (1.6 ± 0.9 % vs −1.7 ± 0.6 %, p = 0.005), and functional performance (p < 0.05), compared to controls (n = 16). Compliance has been >87 %. There have been no injuries. Conclusions Brief supervised HiPRT with impact loading is a safe and effective exercise therapy for postmenopausal women with low to very low bone mass.